36.5k views
4 votes
Simplify

2(a-3)+4b-2(a-b-3)+5​

User FileX
by
4.5k points

2 Answers

7 votes

Answer:

6b + 5

Explanation:

2(a -3) + 4b - 2(a - b -3) + 5

2 * a = 2a

2 * -3 = -6

2a - 6 + 4b - 2(a - b - 3) + 5

-2 * a = -2a

-2 * -b = 2b

-2 * -3 = 6

2a - 6 + 4b - 2a + 2b + 6 + 5

Combine like terms

2a - 2a = 0

-6 + 4b + 2b + 6 + 5

4b + 2b = 6b

-6 + 6b + 6 + 5

-6 + 6 + 5 = 5

6b + 5

User AvMishra
by
5.1k points
0 votes

Hey!

-------------------------------------------------

Solve:

= 2(a - 3) + 4b - 2(a - b - 3) + 5

Distributive Property:

= 2a - 6 + 4b - 2a + 2b + 6 + 5

Combine Like Terms:

= (2a - 2a) + (4b + 2b) + (6 - 6 + 5)

Simplify:

= (0a) + 6b + 5

Answer:

= 6b + 5

-------------------------------------------------

Hope This Helped! Good Luck!

User Sanjary
by
5.5k points